Analisis Cerpen "Harta Gantungan" Karya Ahmad Tohari dengan Pendekatan Religius - Kairiyah, Annisatul; Abdurrahman, Abdurrahman (TSAQOFAH, 2026)
Literary works that represent the lives of the marginalized through a religious perspective play an important role in revealing the relationship between social experience and spirituality, yet studies that specifically examine the construction of religious values in Ahmad Tohari’s short story Harta Gantungan remain relatively limited. This study aims to analyze the religious values in the short story using a religious approach by examining how spiritual, moral, and Islamic teachings are expressed through character depiction, plot, setting, and symbolic elements of the narrative. The study employs a qualitative descriptive method through close reading of the text and interpretation of its embedded meanings. The analysis shows that the elderly woman living in poverty is portrayed as possessing inner wealth through her sincerity (ikhlas), patience (sabar), and piety (taqwa) toward God; the short story reflects Islamic values such as sabar, ikhlas, syukur, qana’ah, and tawakal, which serve as the moral foundation of the main character in facing life’s hardships. In addition, the symbol of the “suspended wealth” (harta gantungan) functions as a spiritual marker of the transience of the material world and the importance of good deeds as provision for the hereafter. With a simple yet deeply meaningful language style, Ahmad Tohari successfully conveys religious messages in a subtle and humanistic manner through the everyday realities of rural communities, thereby enriching the corpus of Indonesian Islamic literature and contributing to the strengthening of religious literary studies rooted in the lives of ordinary people.